Analisis Pengaruh QRIS terhadap Sistem Informasi Pembayaran Digital dan Perilaku Pengguna di Indonesia - Ryantina, Dessyanti; Arinal, Veri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study analyzes the influence of QRIS (Quick Response Code Indonesian Standard) on digital payment information systems and user behavior in Indonesia. The research method uses a quantitative approach with simple linear regression analysis and validity-reliability tests. Data were collected through online questionnaires from 130 QRIS users at STIKOM CKI Campus. The results indicate that QRIS significantly affects the efficiency of digital payment systems, with regression coefficients of 0.8334 for ease of use and 0.0794 for security. Additionally, QRIS usage frequency influences user satisfaction (β = 0.462). Descriptive analysis reveals that 61.5% of respondents recommend QRIS, with the main constraint being slow internet connections (46.2%). These findings provide practical implications for service providers and regulators to enhance QRIS adoption.
Keywords: QRIS; Information System; Digital Payment